Experimental investigation into stationary operated, thermochemical recuperation applied to a 200 kW industrial scale oxy-fuel furnace. (25th July 2022) - Wachter, Philipp; Hödl, Philipp; Raic, Juraj; Gerald, Wieser; Gaber, Christian; Demuth, Martin; Hochenauer, Christoph
Abstract: Efficiency optimizations of industrial processes will play a key role in future actions reducing the global greenhouse gas emissions. This also applies to the industrial high temperature sector whereby the approach of thermochemical recuperation (TCR) is promising for such applications. The current paper thus presents the first report of experimental investigations into TCR in industrial scale (200 kW power input) and in recuperative mode with combined steam reforming and partial oxidation of methane applied inside the reactor. In contrast to previous investigations in industrial scale reported, which exclusively focused on regenerative concepts, the use of oxygen as part of the reactants plays a key role with respect to the following aspects: (I) Methane conversion: CH 4 conversion rates higher than 80% were observed for all adjusted operation points. Efficient conversion of methane to syngas was thus provided by the approach. (II) Temperature control: The addition of oxygen influenced the temperature distribution inside the reactor considerably, causing an increase of the average temperature from 771 °C to 801 °C. Consequently, oxygen addition is an appropriate method for temperature control inside the reactor. (III) Efficiency: The furnace power input was increased by a maximum of 12.1% compared to conventional oxy-fuel combustions without TCR. Highlights: The first stationary operated, industrial scale TCR system is presented. High temperature application tests with a power input of 200 kW were performed. The effects of oxygen addition upstream of the reactor were investigated. Temperature measurements alongside the axial reactor axis were analysed. Furnace power input was increased by 12.1% compared to a combustion without TCR. Graphical abstract: